Exploring grief experiences of rangatahi offenders through the kōrero of Māori community leaders : a thesis presented in partial fulfilment of the requirements for a Master of Arts in Psychology at Massey University, Albany campus, New Zealand - Peapell, Nikki Lee (Massey University, 2012)
Māori youth (rangatahi) apprehension and recidivism rates are significantly higher in comparison to non-Māori, which impacts negatively on their health and well-being, as well as their whānau and wider communities. Unresolved grief is a possible factor which contributes to these high rates of offending, especially where troubled rangatahi do not have access to traditional grieving practices such as tangihanga (funeral rituals). This project seeks to establish a foundation for a larger project that gives voice to rangatahi offenders’ experiences of grief. Toward this aim, the thesis interviewed Māori community leaders who have worked with youth offenders and their whānau in a variety of ways, who are also actively engaged in Te Ao Māori (the Māori world), and work amongst their communities. Their cultural competencies suggest they have had access to traditional grieving practices throughout their lives. A kaupapa Māori (Māori cultural ideologies) approach underpins this research project, using narrative inquiry to explore the kōrero of Māori community leaders. Focus lies with a particular interest in their personal experiences of grief; knowledge of traditional grieving rituals and practices; and their understanding and guidance for rangatahi offenders who may have limited access to traditional healing processes. The in-depth interviews were collected, and systematically analysed to produce texts of grief and hope. Through interviewing Māori community leaders and acknowledging their role as facilitators of knowledge, a rich foundation was established to enable development of the subsequent project in a space of safe guidance. The leaders move back and forth from Te Ao Māori to Te Ao Hurihuri (the modern world) in a way that provides them with the resources required to be successful in their roles, and able to create positive development amongst our rangatahi and their whānau. By connecting past wisdoms with present circumstances, a forum can be created in which we can reflect on our current roles and relationships with rangatahi offenders. It may then be possible to help create a future where rangatahi offenders are nurtured and empowered to create positive futures for themselves.
Keywords: Maori youth offenders; Maori recidivists; Effect of grief on recidivsm; Maori grief; Maori community leaders; Experiences of grief; Rangatahi